Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Return on Assets pada PT Blue Bird Tbk: he Effect of Current Ratio and Debt to Equity Ratio on Return on Assets at PT Blue Bird Tbk - Nurlaila Nurlaila; Kresensia Lipa Sudi; Genoveva Salu; Gracasanda Daniella; Syahrillah Anwari (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
Return on Assets is one of the indicators used to assess a company’s ability to manage its resources and achieve its business objectives. This study aims to determine the effect of the Current Ratio and the Debt-to-Equity Ratio on Return on Assets at PT Blue Bird Tbk, both partially and simultaneously. This study employs a quantitative approach using secondary data obtained from PT Blue Bird Tbk’s financial statements for the period 2018–2025. The data analysis techniques used include classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) using SPSS 27. The results show that the Current Ratio has a significant effect on Return on Assets with a significance value of 0.002, while the Debt-to-Equity Ratio also has a significant effect with a significance value of < 0.001. Simultaneously, the Current Ratio and Debt-to-Equity Ratio have a significant effect on Return on Assets with a significance value of < 0.001. The Adjusted R-Square value of 0.395 indicates that these two variables explain 39.5% of the variation, while the remaining 60.5% is influenced by other factors outside the scope of this study. The findings of this study indicate that liquidity management and a balanced capital structure are important factors in improving the efficiency of a company’s asset utilization. Therefore, management needs to optimize current assets and maintain debt at a healthy level to ensure the company’s profitability.